Inventory Control in Multi-Supplier System under Quantity Discount with Deteriorating Inventory - Tengku Muhamad Rozi, Tengku Sofia Zulaikha; Muhammad Basri, Cik Sri Mazzura (Enhanced Knowledge in Sciences and Technology, 2024)
In today’s uncertain economy, businesses navigate strategies for growth amid challenges in managing perishable products, known for their short lifespan and declining value. Effective coordination among multiple suppliers and utilizing quantity discounts optimizes supply chain profits. Systematic inventory management is crucial for identifying efficient order quantities, optimal supplier combinations, and cost-effective discounts, ultimately reducing overall inventory costs. This study explores how quantity discounts impact deteriorating inventory and seeks suppliers maximizing profits while minimizing inventory expenses. The model focuses on integrating quantity discounts into inventory systems for items with fixed lifetimes following the Weibull distribution. Utilizing discounts to spur demand and control deterioration, the model is validated through MATLAB and Excel analysis for critical supply chain parameters. An illustrative example with two suppliers offering distinct quantity discounts demonstrates model practicality. The findings aid decision-making in perishable product supply chains, shedding light on optimizing total costs amidst parameter variations.